Influence of cathode materials on thermal characteristics of lithium-ion batteries - Yuan, Yuan; Ma, Qian; Zhang, Xiangqian; Zhang, Fan; Song, Xiangning; Xin, Hongchuan; Zhu, Guiru; Zhang, Hongzhe (Frontiers in Chemistry, 2024)
In this work, the thermal stability of four types of 18,650 lithium-ion batteries with LiCoO2 (LCO), LiFePO4 (LFP), LiNi0.8Co0.1Mn0.1O2 (NCM811) and LiNi0.8Co0.15Al0.05O2 (NCA) materials as cathodes are experimentally investigated by the accelerating rate calorimeter (ARC) and the isothermal battery testing calorimeter (iso-BTC) under adiabatic and isothermal conditions, respectively. The thermal runaway danger level of these batteries can be ranked as LCO > NCA > NCM811 >> LFP by judging from the values of Tmax and HRmax, nominal. The higher the nickel and cobalt content, the higher the lithium-ion battery capacity, but the worse the thermal stability. The Qtotal of NCA is the largest in the complete standard charge and discharge process, due to that the capacity of NCA is significantly higher than that of the other three batteries, resulting in remarkable increase in Qirre proportioned to the square of the current. When the ambient temperature rises, the energy release decreases owing to the decrease in the internal resistance of the battery. These studies are expected to have important implications for the subsequent safe design of commercial lithium-ion batteries with different cathode materials.